Feasibility of Homeopathic Treatment for Symptom Reduction in an Integrative Oncology Service. (June 2018) - Samuels, Noah; Freed, Yakov; Weitzen, Rony; Ben-David, Merav; Maimon, Yair; Eliyahu, Uri; Berger, Raanan
Background: Homeopathy has the potential to reduce symptoms related to cancer treatment. The present study examined the feasibility of a homeopathic consultation and treatment program, provided as part of an integrative oncology service.Methods: The electronic medical files of patients undergoing a homeopathic consultation in an integrative oncology service clinic were examined retrospectively. Adherence to the homeopathic treatment regimen and perceived response to the treatment were evaluated.Results: The files of 124 patient (34 males, 90 females) were examined, of which two-thirds reported acquiring and self-administering the homeopathic remedy as prescribed, and nearly three-quarters reporting a beneficial effect. Adherence to the homeopathic treatment regimen was greatest among patients attending a second visit, as opposed to having only telephone/e-mail follow-up ( P < .005). An association was found between a perceived beneficial effect of treatment with attending a follow-up visit ( P = .04), female gender ( P = .02), younger age ( P = .048), diagnosis of breast cancer ( P = .014), and current radiation treatment (vs chemotherapy; P = .003). Patients reporting chemotherapy-induced peripheral neuropathy were also more likely to report a beneficial effect ( P = .004), as were female patients reporting hot flashes ( P = .005) and those referred by an oncologist ( P = .046). No adverse effects were attributed to the homeopathic treatment.Conclusions: Homeopathy can be successfully incorporated within a supportive care integrative oncology service. In addition to demographic and cancer-related characteristics, as well as symptoms, patients attending a second visit (vs only telephone/e-mail follow-up) were more likely to adhere to and perceive a beneficial effect from the homeopathic regimen.